A Hot-spot of In-frame Duplications Activates the Oncoprotein AKT1 in Juvenile Granulosa Cell Tumors - Laurianne Bessière; Anne-Laure Todeschini; Aurélie Auguste; Sabine Sarnacki; Delphine Flatters; Bérangère Legois; Charles Sultan; Nicolas Kalfa; Louise Galmiche; Reiner A. Veitia (EBioMedicine, 2015)
Background: Ovarian granulosa cell tumors are the most common sex-cord stromal tumors and have juvenile (JGCTs) and adult forms. In a previous study we reported the occurrence of activating somatic mutations of Gαs, which transduces mitogenic signals, in 30% of the analyzed JGCTs. Methods: We have searched for alterations in other proteins involved in ovarian mitogenic signaling. We focused on the PI3K–AKT axis. As we found mutations in AKT1, we analyzed the subcellular localization of the mutated proteins and performed functional explorations using Western-blot and luciferase assays. Findings: We detected in-frame duplications affecting the pleckstrin-homology domain of AKT1 in more than 60% of the tumors occurring in girls under 15 years of age. The somatic status of the mutations was confirmed when peritumoral DNA was available. The JGCTs without duplications carried point mutations affecting highly conserved residues. Several of these substitutions were somatic lesions. The mutated proteins carrying the duplications had a non-wild-type subcellular distribution, with a marked enrichment at the plasma membrane. This led to a striking degree of AKT1 activation demonstrated by a strong phosphorylation level and by reporter assays. Interpretation: Our study incriminates somatic mutations of AKT1 as a major event in the pathogenesis of JGCTs. The existence of AKT inhibitors currently tested in clinical trials opens new perspectives for targeted therapies for these tumors, which are currently treated with standard non-specific chemotherapy protocols.